FUNGOS MICORRÍZICOS NATIVOS EM TIFTON 85 (CYNODON SPP) SOB DIFERENTES SISTEMAS DE CULTIVO - ANTONOW, GUSTAVO; BURATTI, JOAO V.; BERTO, JORGE L.; LIBARDONI, JULIANA; BATTAGLIN, RAQUEL F.; FERNADES, SANDRA B. V.; FERNANDES, SANDRA B. V.; QUADROS, VALMIR J. D. (Salão do Conhecimento, 2013)
Resumo